Proceedings of the international CANeW table ronde : İstanbul, 23-24 November 2001 : Central Anatolian neolithic e-workshop : the neolithic of Central Anatolia : internal developments and external relations during the 9th-6th millennia cal bc (İstanbul)
vii, 348 s.